The Kim –Trump Summit in Singapore : North Korea’s End Goals - Singh, Bhubhindar (2018)
North Korea’s strong willingness to engage in active diplomacy has raised hopes for a ‘new era of peace’ on the Korean Peninsula. While many are wondering about Pyongyang’s intentions, two goals are driving the regime: legitimacy and reunification.